Smernice za izobraževanje v zdravstveni negi na študijskem programu prve stopnje Zdravstvena nega (VS) - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2015)
Introduction: Education in nursing in the European Union member states is regulated by the Directive 2013/55/EU. In Slovenia, the national directives as an upgrade to the European directives have as yet not been developed. Furthermore, in the last decades the needs for nursing education have not been explored into. Methods: A complementary combination of qualitative consensus methods (panel group of experts, techniques of group consensus), qualitative non-experimental descriptive method Delfi and the literature review were utilised in the development of the directives. The representatives of higher educational and health institutions, national nursing association, and nursing students participated in the project. Results: The process of development of directives lasted from 2013 till 2015. It encompassed 6 iterations of different consensus methods. More than 150 nursing experts participated in this process who were chosen by the snowball sampling technique and according to their institution affiliation (higher educational and healthcare institutions), and 18 nursing students. The total of 8 content-related directives were identified. Conclusion and implementation: The directives present a solid basis for unification of nursing education in the Republic of Slovenia. They present the foundation for the evaluation of nursing education on the basis of which responsible political decisions may be reached relating to the quality and quantity of higher nursing education.
Keywords: diplomirana medicinska sestra; diplomirani zdravstvenik; Directive 2013/55/EU; Direktiva 2013/55/EU; education; izobraževanje; kakovost; nursing; quality; registered nurse; zdravstvena nega